2011
DOI: 10.3892/ol.2011.414
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PPARγ and PTEN in human colorectal cancer: An immunohistochemical study using tissue microarray methodology

Abstract: Abstract. Although aberrations of peroxisome proliferatoractivated receptor γ (PPARγ) and phosphatase and tensin homolog (PTEN) expression have been identified in several other cancer types, certain previous studies have revealed that PPARγ is abundant in normal and malignant tissue in the colon. The question of whether aberrant PTEN is involved in the initial stage or is a later event during colorectal carcinogenesis remains controversial. Relatively few studies have focused on the correlation of expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
6
22
2
Order By: Relevance
“…They also reported, similarly to the present study, some well-defined differences in PTEN expression between normal colonic mucosa, adenomatous polyps and CRC. Such a relationship has been noted by other authors as well [21,22].…”
Section: Pten Expression Profiles Of Adenomas and Adenocarcinomassupporting
confidence: 83%
“…They also reported, similarly to the present study, some well-defined differences in PTEN expression between normal colonic mucosa, adenomatous polyps and CRC. Such a relationship has been noted by other authors as well [21,22].…”
Section: Pten Expression Profiles Of Adenomas and Adenocarcinomassupporting
confidence: 83%
“…Weak expression (cytoplasm and nuclear staining) of PTEN is associated with liver metastasis and poor patient survival in CRC . Similarly, PTEN expression is positively associated with histological grades and distant metastases in CRC . It is well know that PTEN protein plays an important role in cell growth, apoptosis, migration, invasion, and adhesion by negatively regulating several signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, other reports have indicated that the loss of PTEN might reflect tumor aggressiveness. 10,11 However, in a series of 173 patients receiving second-or greater line cetuximab treatment, PTEN status was reported to correlate only with overall survival (OS) but not with response or PFS. 12 These findings raise the question of whether the loss of PTEN expression might be a predictive marker of outcome after anti-EGFR treatment or a prognostic marker to identify patient outcomes, regardless of the treatment response.…”
Section: Introductionmentioning
confidence: 99%